A Case of Iatrogenic Pseudoaneurysm Caused by EGBS and Penetrating the Cystic Duct - Habu, Takumi; Sako, Akihiro; Nishida, Kotaro; Maruyama, Takehito; Matsui, Yuichi; Komatsu, Koichi; Arakawa, Keiichi; Aoki, Shigeo; Mishima, Hideyuki (Nippon Shokaki Geka Gakkai zasshi, 2021)
An 82-year-old male underwent endoscopic choledocholithotomy and endoscopic gallbladder stenting (EGBS) for acute cholecystitis with choledocholithiasis. Cholecystitis subsided and he was discharged from hospital. However, CT performed for hematemesis 30 days after stenting revealed a pseudoaneurysm in the right hepatic artery, suggesting penetration of the cystic duct. On the same day, the patient was diagnosed with hemobilia due to penetration of the pseudoaneurysm and underwent open hemostasis and cholecystectomy. Subsequently, he was discharged again because of the absence of intra-abdominal complications. The pseudoaneurysm was located adjacent to the stent and was penetrated, resulting in hematemesis and melena. This can be explained by mechanical stimulation, implicating an iatrogenic injury due to EGBS. We herein report a rare case of an iatrogenic pseudoaneurysm that was caused by EGBS and may have been penetrated during the procedure.